Tromsø museums aarshefter. - Tromsø museum. (Tromsø : C. Hansen, 1878)
Imprint varies. Title varies slightly: v. 41-50 have title: Tromsø museums årshefter. Some no. published out of chronological sequence. Issue numbering begins with v. 40; some no. issued in combined form; no. of issues per v. varies. Mode of access: Internet. Vols. 1 (1878)-25 (1901) with v. 25; v. 26 (1902)-45 (1922) with v. 45 (includes index to other publications of the Museum). Split into: Tromsø museums aarshefter. Humanistisk avd., and: Tromsø museums aarshefter. Naturhistorisk avd.